A two-step combination strategy for significantly enhancing the interfacial adhesion of CF/PPS composites: The liquid-phase oxidation followed by grafting of silane coupling agent. (15th June 2020) - Hu, Jiqiang; Li, Fei; Wang, Bing; Zhang, Hanqi; Ji, Chunming; Wang, Shixun; Zhou, Zhengong
Abstract: Due to low activity and poor wettability, the fiber-matrix interface is weak area, which seriously affects the mechanical properties of fiber reinforced polymer (FRP) composites. This paper focuses on the improvement of the interfacial adhesion of carbon fiber fabric reinforced polyphenylene sulfide (CF/PPS) composites. A two-step combination strategy, including liquid-phase oxidation and grafting of silane coupling agents (SCAs), is developed to modify CF surfaces. The tensile strength, flexural strength and interlaminar shear strength (ILSS) of CF/PPS composites with modified CFs increased by 5.96%, 36.18% and 21.73%, respectively. And the enhancement mechanism of the modification method established is revealed. Scanning electron microscope (SEM) morphologies on fractured surfaces showed that predominant failure mechanisms changed from interface debonding to deformation and break of matrix. This indicates that this modification method is effective for promoting the interface bonding and enhancing the mechanical performances of CF/PPS composites, showing potential for industrialization. Graphical abstract: Image 1 Highlights: Flexural strength and ILSS of CF/PPS composites significantly improved after surface modification of CFs. The mechanism of surface modification of CFs via liquid-phase oxidation and introduction of SCAs was investigated. This modification method provides a new idea for manufacturing FRP composites with superior mechanical properties.